A novel octa-arginine-modified injectable self-assembling peptide hydrogel for multidrug-resistant cancer therapy - Ying Wang; Zhuowen Hao; Bingshu Li; Jianming Tang; Zihui Zhang; Zhi Wang; Lian Yang; Jiaxin Peng; Jingfeng Li; Li Hong (Materials & Design, 2024)
Surgery combined with systemic chemotherapy is currently the main modality of cancer treatment. However, the development of cancer multidrug resistance and inevitable surgical residual lesions lead to high rates of cancer recurrence and mortality. Meanwhile, systemic drug toxic side effects and surgical bleeding complications seriously reduce the quality of life of patients. To avoid cancer multidrug resistance and comprehensively optimize cancer treatment, this work provides a novel injectable cell penetrating peptide octa-arginine (R8)-modified RADA16 (RR) self-assembling peptide nanofiber hydrogel as an anticancer drug carrier for multidrug-resistant cancer therapy. In RR hydrogel, highly compatible RADA16 functions as the β-sheet-based self-assembling backbone which tightly adheres to cancer tissue, prevents postoperative bleeding, and sustainedly releases anticancer drugs for long-term effects. The introduced R8 motifs endow RR hydrogel with the capacity to selectively kill cancer cells and reverse cancer multidrug resistance, which minimally impact normal tissue cells. Specifically, R8 motifs on the hydrogel scaffold selectively interfere with cancer cell membranes, increase drug uptake and penetration into cancer cells and tissues by enhancing multiple internalization pathways, and reduce drug efflux by inhibiting P-gp and BCRP multidrug-resistant transporters. Therefore, this study provides a multifunctional hydrogel material with strong potential for multidrug-resistant cancer clinical translation.